Transparent conducting SnO2 thin films synthesized by nebulized spray pyrolysis technique: Impact of Sb doping on the different physical properties. (January 2021) - Hossain, Md. Faruk; Shah, Md. Abdul Hadi; Islam, Md. Ariful; Hossain, Md. Sazzad
Abstract: The impact of antimony (Sb) doping concentration on the different physical properties of transparent conducting tin oxide (SnO2 ) thin films synthesized through nebulized spray pyrolysis (NSP) method have been explored systematically. X-ray diffraction (XRD) results reveal the tetragonal cassiterite structure of single phase SnO2 and the decrement of crystallite size with rising Sb doping concentration. Uniform and compact surface morphology with continuous distribution of grains and reduction of grain size with increasing dopant amount are illustrated by scanning electron microscopy (SEM). The stoichiometry of SnO2 film with 2% Sb doping is confirmed by energy dispersive X-ray spectroscopy (EDS) study. The optical transmittance is more than 85% in the visible region for undoped film and enhanced in the near infrared (NIR) spectral region for all the films. The transparency is reduced and the optical band gap is found to increase from 3.69 eV to 3.90 eV upon Sb inclusion. The extinction coefficient, refractive index, dielectric constant, dissipation factor, volume energy loss function, surface energy loss function, optical conductivity and optical density of the films are determined and interpreted for different dopant concentrations. The photoluminescence (PL) spectrum demonstrates the enhancement of emission intensity with increasing Sb incorporation representing its suitability in the application of solid state lighting. The lowest resistivity of 6.435 × 10 −4  Ω cm and the highest carrier concentration of 1.316 × 10 21  cm −3 are achieved for the film with 8% Sb doping concentration. The mobility of the studied degenerated films is varied from 54.743 cm 2 /Vs for undoped films to 7.378 cm 2 /Vs for 8% Sb doped film and limited by ionized impurity scattering. The film deposited with 2% Sb doping level exhibits the highest figure of merit values in both visible and NIR wavelength region indicating its better role in optoelectronic applications. Highlights: Undoped and Sb doped SnO2 thin films have been successfully synthesized by NSP technique. Crystallite size as well as the grain size are reduced upon Sb inclusion as observed by XRD and SEM, respectively. The average transmittance of the films is greater than 74% in the visible region and enhanced in the NIR region. The obtained values of conductivity and sheet resistance are suitable for TCO applications. The highest figure of merit is exhibited by 2% Sb doping film in both visible and NIR region.